Adrenal haemorrhage due to heparin-induced thrombocytopenia - Ketha, Siva; Smithedajkul, Patrick; Vella, Adrian; Pruthi, Rajiv; Wysokinski, Waldemar; McBane, Robert (Thrombosis and Haemostasis, 2013)
Adrenal haemorrhage (AH) is a rare but potentially devastating complication of heparin-induced thrombocytopenia (HIT). Neither the prevalence nor the natural history of AH due to HIT are known. The objectives of this study were to identify the spectrum of AH causes, to characterise the frequency of AH due to HIT and determine the natural history of HIT-associated AH. All patients with incident adrenal haemorrhage from January 2002 through June 2012 seen at the Mayo Clinic were identified. Over this time frame, there were a total of 115 patients with AH of which 11 cases (10%; mean age 67 ± 8 years; 73% female) were associated with HIT. Of these, all but one occurred in the postoperative setting and involved both adrenal glands (89%) with acute adrenal insufficiency at the time of diagnosis. Cases were found incidentally during an evaluation for fever, shock, abdominal pain or mental status changes. All HIT patients experienced venous thrombosis at other locations including deep venous thromboses (n=14), pulmonary emboli (n= 4) and arterial thrombosis (n=2). Four patients undergoing total knee arthroplasty had “spontaneous HIT” with AH in the absence of identifiable heparin exposure. Other causes of AH included trauma (29%), sepsis (15%), antiphospholipid antibody syndrome (10%), and metastatic disease (12%). In conclusion, AH is an important but seldom recognised presumed thrombotic complication of HIT, which usually occurs in the postoperative period, especially after orthopaedic procedures. This syndrome can occur in the apparent absence of heparin exposure, especially following major joint replacement surgery.
Keywords: HIT; heparin; adrenal haemorrhage; Warkentin 4T Score; anticoagulation